Representing Future Situations of Service: Prototyping in Service Design - Blomkvist, Johan (Linköping University, 2018)
The dataset describes situated cognition as a lens to describe prototyping in service design and consists of audio and video files:

Audio files in MP3 format compressed in zip format.

Audio files in M4B format compressed in zip format.

Video presentation of Ph.D. thesis.

The dataset was originally published in DiVA and moved to SND in 2024.

Datasetet handlar om situerad kognition som lins för att beskriva prototypande i tjänstedesign och består av ljud och video filer:

Ljudfiler i format MP3 komprimerade i zip-format.

Ljudfiler i formatet M4B komprimerade i zip-format.

Videopresentation av Ph.D. avhandling.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Representationer av Framtida Tjänster: Prototypande i Tjänstedesign
Representationer av Framtida Tjänster
Keywords: prototyping; prototypande; service design; tjänstedesign; situated cognition; situerad kognition; representations; representationer; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap